2014
DOI: 10.18632/oncotarget.2152
|View full text |Cite|
|
Sign up to set email alerts
|

Upregulation of microRNA135a-3p and death receptor 5 plays a critical role in Tanshinone I sensitized prostate cancer cells to TRAIL induced apoptosis

Abstract: Though tumor necrosis factor related apoptosis inducing ligand (TRAIL) has been used as a potent anticancer agent, TRAIL resistance is a hot-issue in cancer therapy. We investigated the antitumor mechanism of Tanshinone I to sensitize prostate cancer cells to TRAIL. Comibination of Tanshinone I and TRAIL exerted synergistic cytotoxicity, increased cleaved PARP, sub G1 population, the number of TUNELpositive cells, activated caspase 8, 9 and ROS production in PC-3 and DU145 cells. Of note, combination of Tanshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…(24)(25)(26)(27)(28)(29)(30) In prostate cancer cells, miR-135a-3p was shown to mimic the enhanced apoptosis induced by death receptor 5 with respect to increased poly(ADP-ribose) polymerase cleavage, Bax expression, and the number of TUNEL-positive cells following cotreatment with tanshinone I and TRAIL. (32) Our present study indicates that miR-135a-3p may also have antitumor activities in ovarian cancer. Human miR-135a is encoded by two genes located on different chromosomes that produce identical active sequences (chromosomes 3 and 12 for miR-135a1 and miR-135a2, respectively).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…(24)(25)(26)(27)(28)(29)(30) In prostate cancer cells, miR-135a-3p was shown to mimic the enhanced apoptosis induced by death receptor 5 with respect to increased poly(ADP-ribose) polymerase cleavage, Bax expression, and the number of TUNEL-positive cells following cotreatment with tanshinone I and TRAIL. (32) Our present study indicates that miR-135a-3p may also have antitumor activities in ovarian cancer. Human miR-135a is encoded by two genes located on different chromosomes that produce identical active sequences (chromosomes 3 and 12 for miR-135a1 and miR-135a2, respectively).…”
Section: Discussionsupporting
confidence: 53%
“…Many studies have investigated the relationship between miR-135a-5p and cancer, (24)(25)(26)(27)(28)(29)(30) but have not examined miR-135a-3p. (31,32) MicroRNA-135a-5p has often been reported to function as a potential tumor suppressor. (24)(25)(26)(27)(28)(29)(30) In prostate cancer cells, miR-135a-3p was shown to mimic the enhanced apoptosis induced by death receptor 5 with respect to increased poly(ADP-ribose) polymerase cleavage, Bax expression, and the number of TUNEL-positive cells following cotreatment with tanshinone I and TRAIL.…”
Section: Discussionmentioning
confidence: 99%
“…reported that endothelial expression of Drp1 and Fis1 increased and Opa1 decreased in diabetes mellitus with alterations in mitochondrial networks, ROS production, endothelial nitric oxide synthase (eNOS) activation, and cyclic guanosine monophosphate (cGMP) production36. Our findings with decrease in tumor size and IHC analysis of CD31 suggested that Tan IIA might inhibit angiogenesis associated with down regulation of ROS3738 through mitochondrial dynamics. In the present study, we further confirmed that Tan IIA indeed reduced the levels of Mfn-1, Mfn-2 and Opa-1 and increased the levels of Drp-1 in both osteosarcoma 143B cells and 143B cell xenograft mice.…”
Section: Discussionmentioning
confidence: 57%
“…Although radical prostatectomy, chemotherapy, radiotherapy, high‐intensity focused ultrasound, and hormonal therapy surgery have been used for prostate cancer management, prostate cancer therapy is still limited because of chemo‐resistance and toxicity of anticancer agents. Thus, recently, many natural compounds such as curcumin (Cheng et al ., ), resveratrol (Alkhalaf, , ; Aluyen et al ., ; Whitlock et al ., ), capsaicin (Jung et al ., ), brazilin (Kim et al ., ), tanshinone I (Shin et al ., ), tanshinone IIa (Yun et al ., ), ursolic acid (Song et al ., ), coumestrol (Cho et al ., ), isothiocyanates (Gupta et al ., ), ginkgetin (You et al ., ), and auraptene (de Medina et al ., ) became attractive because of their efficacy and less toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Although radical prostatectomy, chemotherapy, radiotherapy, highintensity focused ultrasound, and hormonal therapy surgery have been used for prostate cancer management, prostate cancer therapy is still limited because of chemo-resistance and toxicity of anticancer agents. Thus, recently, many natural compounds such as curcumin (Cheng et al, 2013), resveratrol (Alkhalaf, 2007a(Alkhalaf, , 2007bAluyen et al, 2012;Whitlock et al, 2011), capsaicin (Jung et al, 2014), brazilin , tanshinone I (Shin et al, 2014), tanshinone IIa (Yun et al, 2013), ursolic acid (Song et al, 2012), coumestrol (Cho et al, 2014), isothiocyanates (Gupta et al, 2014), ginkgetin (You et al, 2013), and auraptene (de Medina et al, 2010) became attractive because of their efficacy and less toxicity. Auraptene (7-geranyloxycoumarin) contained in Ferula and Citrus fruit (Soltani et al, 2010) has been shown to have antiinflammatory, anti-protozoal, anti-fungal, anti-bacterial, anti-oxidative, and immunomodulatory effects (Epifano et al, 2008;Takahashi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%